Rwanda government adopts and integrates animal source foods consumption communication materials into the national maternal and child nutrition curriculum to improve nutrition outcomes - CGIAR Research Program on Livestock (2020)
ILRI and its partners have implemented a social and behavior change communication intervention on animal source foods consumption, particularly the drinking of milk among Girinka households in Rwanda. This was implemented through a Feed the Future Innovations Labs for Livestock Systems (LSIL) research project. In 2020 the national counselling cards were updated to include animal source foods consumption messages, which have been validated through the National Child Development Agency and are now being used nationally by community health workers.